Perancangan Strategi Usaha Berbasis Analisis Lingkungan Internal dan Eksternal pada UMKM Ayam Ketumbar Hasanah - Mutqi Sopiawadi; Dandi Muhammad Rizky; Eka Marlianaa; Imelda Sari; Novia Rizky Azzahra; Nurul Ayudia Hartanti; Nico Mei Xeastro Limbong (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to design a business strategy for Hasanah Coriander Chicken MSME based on internal and external environmental analysis to improve business competitiveness and sustainability. The study uses a qualitative descriptive method with a case study approach through in-depth interviews and documentation studies. The analysis was conducted using a strategic management framework that included RBV, PESTEL, as well as IFAS, EFAS, SWOT, and IE matrices. The results showed that the main strengths of the business lie in the distinctive taste of its products and the use of digital platforms, while its weaknesses lie in its limited production capacity and business management. Externally, the digital market offers considerable opportunities, but these are offset by intense competition and fluctuations in raw material prices. The business's strategic position is one of hold and maintain, so selective development is recommended through strengthening product quality, optimizing digital marketing, and improving operational efficiency.